The development of the word forming models of the adverbial adverbs in the East Slavic Language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The syntactic nature of origin of word forming models of adverbial adverbs in the history of east Slavic languages was substantiated.
Keywords: derivation; adverbalization; morphosyntax way; historic word forming; word forming model; East Slavic Languages